The Pharmacological Potential of Algal Polysaccharides in Food Applications and Chronic Disease Management - Xue Wu; Yuxin Guo; Congjie Dai; Chao Zhao (Future Pharmacology)
Algal polysaccharides are a kind of bioactive compound with diverse pharmacological applications, yet their structure–activity relationships and therapeutic potential in chronic disease management remain systematically underexplored. This review comprehensively analyzes the structural characteristics of brown, red, and green algal polysaccharides, revealing how specific structural features—such as glycosidic linkage patterns and sulfate group positioning—dictate their biological activities. We also demonstrated their multifaceted roles in diabetes, cancer, and cardiovascular diseases through distinct mechanisms, including gut microbiota modulation via short-chain fatty acid production, antioxidant enzyme activation, and targeted inhibition of pathological signaling pathways like mTOR and JAK-STAT3. The work further evaluates extraction methodologies, highlighting the advantages of emerging techniques such as enzyme-assisted and ultrasonic extraction for preserving bioactive integrity. By integrating fundamental research with practical applications in functional foods, this synthesis provides critical insights for harnessing algal polysaccharides in precision nutrition and sustainable biomedicine, while identifying key challenges in standardization and environmental safety that warrant future investigation.